Serum vitamin C levels modulate the lifespan and endoplasmic reticulum stress response pathways in mice synthesizing a nonfunctional mutant WRN protein. Issue 7 (8th February 2018) - Aumailley, Lucie; Dubois, Marie Julie; Brennan, Tracy A.; Garand, Chantal; Paquet, Eric R.; Pignolo, Robert J.; Marette, Andre; Lebel, Michel
Abstract : Werner syndrome (WS) is a premature aging disorder caused by mutations in a RecQ‐family DNA helicase (WRN). Mice lacking part of the helicase domain of the WRN ortholog exhibit several phenotypic features of WS. In this study, we generated a Wrn mutant line that, like humans, relies entirely on dietary sources of vitamin C (ascorbate) to survive, by crossing them to mice that lack the gulonolactone oxidase enzyme required for ascorbate synthesis. In the presence of 0.01% ascorbate (w/v) in drinking water, double‐mutant mice exhibited a severe reduction in lifespan, small size, sterility, osteopenia, and metabolic profiles different from wild‐type (WT) mice. Although increasing the dose of ascorbate to 0.4% improved dramatically the phenotypes of double‐mutant mice, the metabolic and cytokine profiles were different from age‐matched WT mice. Finally, double‐mutant mice treated with 0.01% ascorbate revealed a permanent activation of all the 3 branches of the ER stress response pathways due to a severe chronic oxidative stress in the ER compartment. In addition, markers associated with the ubiquitinproteasome‐dependent ER‐associated degradation pathway were increased. Augmenting the dose of ascorbate reversed the activation of this pathway to WT levels rendering this pathway a potential therapeutic target in WS.—Aumailley, L., Dubois, M. J., Brennan, T. A., Garand, C., Paquet, E. R., Pignolo, R. J., Marette, A., Lebel, M. Serum vitamin C levels modulate the lifespan and endoplasmic reticulum stress response pathways in mice synthesizing a nonfunctional mutant WRN protein. FASEB J. 32, 3623–3640 (2018). www.fasebj.org